Challenges and Teacher Efforts in Facing Independent Curriculum at RA. Munawwarah - Sari , Mutia; Ayunita, Riska; Amalia, Rizka (Global Education Journal, 2025)
Early childhood education plays a crucial role in shaping the foundation of a child's development, encompassing cognitive, affective, and psychomotor aspects. In an effort to improve the quality of education in Indonesia. This study aims to examine the extent of teachers' enthusiasm in implementing the Independent Curriculum, challenges in understanding curriculum content, limitations of technological infrastructure in schools, and the role of teachers and school leaders in overcoming these problems. This research method uses a qualitative approach with a case study design at RA. Munawwarah, data was collected through observation, in-depth interviews, and documentation. The research findings revealed that teachers showed high enthusiasm for the Independent Curriculum, but they still faced obstacles, especially in understanding new concepts such as Learning Outcomes, Learning Objectives, and differentiated learning, as well as limitations in digital devices such as projectors and other supporting technologies. To overcome these challenges, teachers actively participate in training and professional development programs. The principal plays an important role through supportive leadership, continuous evaluation, and the creation of a conducive learning environment.